Comparação do peso dos quelípodos e crescimento em duas espécies de sirís do gênero Callinectes (Brachyura, Portunidae) - Guerrero-Ocampo, Cecilia Margarita [UNESP]; Negreiros-Fransozo, Maria Lucia [UNESP]; Costa, Tânia Marcia [UNESP] (FapUNIFESP (SciELO), 1998)
A comparison of the cheliped's weight in two species of the genus Callinectes was accomplished. The species C. danae e C. ornatus were collected by two otter trawl in Ubatuba bay (23°26' S and 45°02' W). The allometric constants obtained from the regression adjusted to a power function (Y = aXb) were analyzed. These species presented different allometry degrees for each sex considered. The relation PQ x PC presented positive allometry for sex of both species, but male presented higher positive allometry than female. C. danae presented higher positive allometry for chelipeds than C. ornatus. We suggest here that C. danae could be indicated to be submitted to grow out in ponds since it reaches higher size and bigger chelipeds. © 1998, Paraná Institute of Technology Publication.
Keywords: Callinectes; Cheliped; Crescimento relativo; Portunidae; Quelípodo; Relative growth; Siris; Swimming crab